2002
DOI: 10.1126/science.1073776
|View full text |Cite
|
Sign up to set email alerts
|

Signaling of Rat Frizzled-2 Through Phosphodiesterase and Cyclic GMP

Abstract: The Frizzled-2 receptor (Rfz2) from rat binds Wnt proteins and can signal by activating calcium release from intracellular stores. We show that wild-type Rfz2 and a chimeric receptor consisting of the extracellular and transmembrane portions of the beta2-adrenergic receptor with cytoplasmic domains of Rfz2 also signaled through modulation of cyclic guanosine 3',5'-monophosphate (cGMP). Activation of either receptor led to a decline in the intracellular concentration of cGMP, a process that was inhibited in cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
146
0
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(157 citation statements)
references
References 25 publications
7
146
0
4
Order By: Relevance
“…Here we found that β 2 AR/RFz2, which is known to activate non-canonical Wnt signaling (Ahumada et al, 2002), or Wnt5a led to loss of Dishevelled (Figure 5 and 6). Therefore it is conceivable that Gβγ signaling can control both canonical and non-canonical Wnt signaling by determining the amount of Dishevelled at the membrane.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Here we found that β 2 AR/RFz2, which is known to activate non-canonical Wnt signaling (Ahumada et al, 2002), or Wnt5a led to loss of Dishevelled (Figure 5 and 6). Therefore it is conceivable that Gβγ signaling can control both canonical and non-canonical Wnt signaling by determining the amount of Dishevelled at the membrane.…”
Section: Discussionmentioning
confidence: 88%
“…This result is consistent with the previous results (Figure 3) that showed that the DEP domain plays a critical role in the Gβγ mediated degradation of Dishevelled. We next turned our attention to the signaling events occurring after the Frizzled receptor and especially the possible role of phospolipase C (PLC) signaling, which is known to be activated by Gβγ (Ahumada et al, 2002). Addition of a specific PLC inhibitor, u73122 (Lockhart and McNicol, 1999) to cells expressing β 2 AR/RFz1 or β 2 AR/RFz2 and induced with Iso prevented the loss of Dishevelled ( Figure 5D).…”
Section: Activation Of Frizzled Signaling Induces Loss Of Dishevelledmentioning
confidence: 99%
See 1 more Smart Citation
“…WTX, which is vertebrate specific, thus has dichotomic roles in Wnt signaling, analogous to those for Axin and GSK3. The FZD topology invites GPCR comparisons, and FZD coupling to trimeric G-proteins in Wnt/b-catenin signaling has received certain support from pharmacological and genetic studies (Ahumada et al 2002;Katanaev et al 2005;Liu et al 2005;Schulte and Bryja 2007), although this remains a debated issue. Although Gao and Gaq are suggested to regulate Axin-GSK3 interaction (Liu et al 2005), Gbg is shown to be in complex with LRP6, DVL, and Axin and to recruit GSK3 to phosphorylate LRP6 (Jernigan et al 2010).…”
Section: Lrp6 Phosphorylation: Roles Of Pip2 G-protein and Other Kimentioning
confidence: 99%
“…In the Wnt/Ca 2+ pathway, the interaction of noncanonical Wnt ligands and receptors recruits Dvl and G protein and leads to the activation of phospholipase C (PLC), thereby triggering intracellular calcium release. Induced calcium ion flux can activate second messengers such as protein kinase C (PKC), calcium-calmodulin-dependent kinase II (CamKII), or the calcium-dependent phosphatase calcineurin (CaN) (Kuhl et al 2000;Ahumada et al 2002;Sheldahl et al 2003;Kohn and Moon 2005;Ma and Wang 2007). In addition to TAK1/NLK, CamKII can also antagonize the Wnt/b-catenin pathway (Ishitani et al 2003), while activated CaN can dephosphorylate nuclear factor of activated T-cell (NFAT) transcription factors, which can then enter the nucleus and activate their target genes (Murphy and Hughes 2002;Mikels and Nusse 2006).…”
Section: Overview Of Wnt Signaling Pathwaysmentioning
confidence: 99%